Role of CBCT in diagnosis and treatment plan of Impacted teeth: A Case Report - Pradhan, Darpa; Tian, Tang (Orthodontic Journal of Nepal, 2016)
In recent years Cone Beam Computed Tomography (CBCT) has become a widely accepted radiographic tool for diagnosis, treatment planning and follow-up in dentistry. 3D imaging has improved diagnostic efficiency and the practice of dentistry in a variety of ways; from routine evaluation to complex analysis of unusual pathology and congenital deformities. The technology available today makes dentistry better, easier, and more accurate. The most recognized need for CBCT imaging in orthodontics is that of the impacted canine evaluation. This article reports a patient having impacted right maxillary lateral incisor and canine; which is evaluated by 3D CBCT and was found beneficial particularly in terms of anatomical detail of root resorption and labiolingual relationships of the impacted tooth with the roots of neighboring teeth. Linear and angular measurements on CBCT images were accurate and helped in determining the exact location of the impacted teeth making it convenient for the surgical exposure of impacted teet